Pengaruh Kombinasi Diameter Pulley terhadap Uji Fungsi pada Mesin Bubut Multi Purpose Tipe HQ 400 - Sugiarto, Fikri Ariyadhana; Utama, Firman Yasa; Sakti, Arya Mahendra; Abdi, Ferly Isnomo (Universitas Negeri Surabaya, 2023)
Machine tools have a very important role in the industrial sector, especially the manufacturing industry. Various types of machine tools that are often used, one of which is a lathe. Damage that often occurs in the engine drive components, namely the pulley. Therefore, in this study, he was interested in conducting research entitled